2022
DOI: 10.3389/fmed.2022.929096
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygen reduces the incidence of hypoxia in sedated hysteroscopy for assisted reproduction

Abstract: Backgrounds and aimsPain is the main reason for hysteroscopy failure. In day-surgical settings, hysteroscopy procedures are commonly performed with the patient under sedation. Hypoxia is the most common adverse event during sedation and can lead to severe adverse events. This study aimed to compare the incidence of hypoxia when using high-flow nasal oxygen (HFNO) with that when using regular nasal oxygen in patients undergoing hysteroscopy with sedation.Materials and methodsIn this single-center, prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…It can provide heated and humidified, titrated and regulated oxygen concentration via a nasal catheter. Our previous research revealed an advantage of HFNO in reducing the incidence of hypoxia during sedation for hysteroscopy [39]. However, only 1.1% of institutions used HFNO in the practice of sedation of hysteroscopic procedure in our investigation.…”
Section: Discussionmentioning
confidence: 67%
“…It can provide heated and humidified, titrated and regulated oxygen concentration via a nasal catheter. Our previous research revealed an advantage of HFNO in reducing the incidence of hypoxia during sedation for hysteroscopy [39]. However, only 1.1% of institutions used HFNO in the practice of sedation of hysteroscopic procedure in our investigation.…”
Section: Discussionmentioning
confidence: 67%
“…These results were also observed across subgroups, including variations in the type of procedures, the FiO 2 , the hypoxemic profile of the patients, and the mode of propofol administration [35 && ]. Additional indications, such as computed tomography-guided hepatic tumor radiofrequency ablation [36], awake craniotomy [37], and hysteroscopy for assisted reproduction [38], also demonstrated favorable outcomes with the use of HFNO.…”
Section: Key Pointsmentioning
confidence: 99%
“…Additional indications, such as computed tomography-guided hepatic tumor radiofrequency ablation [36], awake craniotomy [37], and hysteroscopy for assisted reproduction [38], also demonstrated favorable outcomes with the use of HFNO.…”
Section: For Which Procedures ?mentioning
confidence: 99%